(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Investigate the most prevalent factors influencing the demand for dental treatment among medical students in Hanoi, establish the correlation between treatment-seeking attitudes and the sociological characteristics of medical students in Hanoi. Materials and Methods: A descriptive cross-sectional study was conducted involving 84 medical students at Hanoi Medical University from August 2024 to January 2024. Results: The majority of students (58.3%) were aged 19-20. Most students sought dental care only when experiencing tooth pain or detecting abnormalities in the mouth (77.4%). Scaling was the most common procedure (57.1%), and most students preferred receiving treatment at private facilities (51.2%). The primary factors when choosing a dentist were professional qualifications, professional attitude, and clinic hygiene standards. Conclusions: The study highlights the multidimensional nature of accessing and utilizing dental care services, with a trend toward seeking care only when problems arise and favoring private dental facilities.